2011
DOI: 10.4049/jimmunol.1000343
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling 1 Regulates Embryonic Myelopoiesis Independently of Its Effects on T Cell Development

Abstract: Suppressor of cytokine signaling 1 (SOCS1) has been shown to play important roles in the immune system. It acts as a key negative regulator of signaling via receptors for IFNs and other cytokines controlling T cell development, as well as Toll receptor signaling in macrophages and other immune cells. To gain further insight into SOCS1, we have identified and characterized the zebrafish socs1 gene, which exhibited sequence and functional conservation with its mammalian counterparts. Initially maternally derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 96 publications
4
16
0
Order By: Relevance
“…2A). It has been suggested that zebrafish SOCS1a plays a regulatory role in erythropoiesis and inflammatory gene expression (30,33). Consistent with this notion, obviously elevated levels of erythropoiesis have been found in socs1a-deficient fish during the early stages, as determined through an assay of gata1 expression at the 24-hpf stage (Fig.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…2A). It has been suggested that zebrafish SOCS1a plays a regulatory role in erythropoiesis and inflammatory gene expression (30,33). Consistent with this notion, obviously elevated levels of erythropoiesis have been found in socs1a-deficient fish during the early stages, as determined through an assay of gata1 expression at the 24-hpf stage (Fig.…”
Section: Resultssupporting
confidence: 69%
“…The zebrafish SOCS1a has been suggested to play roles in hematopoiesis and the IFN signaling pathway similar to those of its mammalian counterpart. It has been demonstrated that the functions of SOCS1a could be mediated by the JAK2-STAT5 pathway (30,33). The results of this study demonstrated elevated levels of phosphorylated STAT5 and hemoglobin mediated via JAK activation in socs1a-null zebrafish compared with the wild-type control fish during their early and adult stages, which confirmed the roles of SOCS1a in activation of the JAK-STAT5 pathway and hematopoiesis (Fig.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is particularly likely for the ortholog of SOCS1, which has been previously shown to regulate mammalian EPOR signaling (2), and the paralogs of SOCS3, which has been demonstrated to be a key in vivo regulator of G-CSFR (64). Indeed, we have previously demonstrated that zebrafish socs1 functions during embryonic hematopoiesis (65). Other mechanisms that may contribute to this transient phenotype remain to be determined, and the role of the cish.b paralog awaits further study.…”
Section: Discussionmentioning
confidence: 99%
“…The negative regulation of cytokine signalling by SOCS involves activation of the JAK2-STAT5 pathway (O'Sullivan et al, 2011). Homologues of all the eight mammalian SOCS family members have been discovered in fish (Wang et al, 2011), while SOCS-1, SOCS-2 and SOCS-3 have been characterized in salmonids (Wang and Secombes, 2008).…”
Section: Introductionmentioning
confidence: 99%